Proposed Enhancement Plan Towards Quality Health Care and Patient Satisfaction in the Colposcopy Clinic - Wang, Ying (International Journal of Public Health and Medical Research, 2025)
Objective: To assess the correlation between the quality of care in colposcopy clinics and patient satisfaction, and to explore personalized optimization paths based on demographic characteristics. Methods: A cross-sectional study design was employed to conduct a multidimensional assessment of 392 patients. Demographic characteristics were analyzed using descriptive quantitative research methods (primarily married, highly educated women aged 30-39, with a hospital stay of 3-5 days), and a structured quality evaluation was conducted across five quality dimensions (equipment resources, treatment processes, infrastructure, doctor-patient interaction, and environmental comfort). Pearson correlation analysis and multiple regression models were used to explore the relationship between quality indicators and satisfaction. Results: The overall patient satisfaction rate was 87%, with the highest recognition for professional competence of medical staff (91%) and process transparency (89%). Satisfaction among patients under 35 years old was significantly lower than that of those aged 35 and above (68.2% vs 92.7%, p<0.01), and satisfaction among those with a bachelor’s degree or higher was significantly lower than that of the lower education group (76.5% vs 88.2%, p=0.03). Patients receiving personalized discharge guidance reported significantly higher satisfaction than those who did not (94.1% vs 73.3%, OR=2.3, 95%CI 1.7-3.1). Scores for the five dimensions of nursing quality (4.2-4.5/5) were strongly positively correlated with satisfaction (r=0.78, p<0.001). Conclusion: This study validated the predictive effectiveness of a structured quality evaluation system on patient satisfaction (explaining 83% of the variance) and confirmed the critical role of personalized services in gynecological care. It is recommended to establish a stratified service plan based on age and education level, enhancing communication mechanisms for younger patients and optimizing the informed consent process for highly educated groups to achieve upgraded precision medical services.